On the DAMA and CoGeNT modulations - Frandsen, M; Kahlhoefer, F; March-Russell, J; McCabe, C; McCullough, M; Schmidt-Hoberg, K (2011)
DAMA observes an annual modulation in their event rate, as might be expected from dark matter scatterings, while CoGeNT has reported evidence for a similar modulation. The simplest interpretation of these findings in terms of dark matter-nucleus scatterings is excluded by other direct detection experiments. We consider the robustness of these exclusions with respect to assumptions regarding the scattering and find that isospin-violating inelastic dark matter helps alleviate this tension and allows marginal compatibility between experiments. Isospin violation can significantly weaken the XENON constraints, while inelasticity enhances the annual modulation fraction of the signal, bringing the CoGeNT and CDMS results into better agreement. © 2011 American Physical Society.